STARTING DATE AZERBAİJAN - Muhammet KEMALOĞLU (Fırat University, 2019)
Time to come to Azerbaijan Turks began to settle very old, and 16 century continued. North Azerbaijani authors, especially in recent times that they reached this conviction and subsequent Azerbaijan became the homeland of the Turks by the old Turks yerlileşmişlerdir mingling with them. Some of the error (Mahmoud Ismailov, etc.). Prototürklerin before the front of the Turks or Asia, Central Asia, göçtüklerini sitting there, and if you write. For example, the late Mehmedov Aydin (1989), and the Nizami Hajiyev Tofik Hudiyev (1990) emphasized the similarity of the words in their books some of the Sumerian-Turkish Turkish race in the formation of the Sumerian civilization write that participate directly or by any means. In this respect, the Turkish scholar Prof. Osman Nedim Tuna research for a long time after the promise of Sumer More than 150 Turkish words in a systematic way to monitor changes in phonetic compared and showed that the former period, the relationship between Sumerian and Turkish languages. 20. F. at the beginning of the century Hommel, examined by comparing the Sumerian-Turkish languages, Sumerian language, considers that the Altaic languages. The famous scholar of contemporary Kazakh-Turkish languages, comparing inspection by the Sumerian Olcas Suleymanov, 60 who found that the word intimacy, and ultimately cultural commitment, and the relationship between the Sumerian language, to prove that the former worked in the Turkish language.